- PENERAPAN TEORI KONSTRUKTIVISME JEAN PLAGET BERBASIS NEUROSCIENCE DALAM PENDIDIKAN DI SMP TAHFIZH INSAN MADANI - Zim, Zim Syamsul Endi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe in depth the integration between Jean Piaget's constructivism theory and the brain-based learning approach in learning practices at SMP Tahfizh Insan Madani Siwi Raya. The constructivism theory itself emphasizes the importance of active student involvement in building knowledge through real experiences and social interactions, while neuroscience provides a scientific understanding of the role of brain conditions, emotions, and the environment in supporting the effectiveness of the learning process. Using a descriptive qualitative approach, data were collected through participant observation, semi-structured interviews with teachers and students, and analysis of learning documentation, then analyzed using the Miles and Huberman interactive model involving the process of data reduction, data presentation, and drawing conclusions systematically. The results of the study showed that teachers actively implemented various learning strategies, such as the use of visual media, problem-based direct experiments, group discussions, and reflective activities, which were in line with the cognitive stages of child development according to Plaget and the basic principles of neuroscience such as fulfilling emotional needs and multisensory stimulation. The learning environment created became more adaptive, flexible, and personal, allowing students to learn optimally according to their cognitive, emotional, and neurological readiness. These findings confirm that harmonious collaboration between constructivism and neuroscience can form a more meaningful, inclusive, responsive, and effective educational approach in supporting holistic development, both from the cognitive, affective, and social aspects of students.